Pengaruh Penerapan Model Pembelajaran PjBL Terhadap Kemampuan Berpikir Kreatif: Peran Rasa Ingin Tahu - Rini, Henny Martha; Azizah, Dewi (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
The purpose of this study is to determine the differences between two models (PjBL and PBL) in terms of curiosity towards creative thinking abilities, as well as to observe the interaction between the learning models in relation to curiosity towards creative thinking abilities. This experimental study used a Posttest Only Control design in a quasi-experiment. The population consisted of 10th grade students at MAN 1 Kota Pekalongan, with a research sample covering class X6 (experimental class) and X7 (control class), which were selected through a simple random sampling technique. Test instruments and questionnaires were used as data collection techniques. The data analysis technique employed was two way ANOVA. Based on the data analysis results, it is shown that , , 3,85) thus rejecting . The conclusion drawn from the analysis is that there are differences in the effects between the PjBL and PBL models in terms of curiosity towards students' creative thinking abilities, and it can be inferred that there is an interaction between the learning models in terms of curiosity towards creative thinking abilities.